2020
DOI: 10.1007/s40430-020-02627-5
|View full text |Cite
|
Sign up to set email alerts
|

Cross-section modeling of the non-uniform corrosion due to chloride ingress using the positional finite element method

Abstract: In this paper, we propose an original and alternative FEM strategy to simulate the expansion and damage in cross sections of concrete elements due to non-uniform corrosion associated with chloride ingress. The strategy embed two-dimensional particle elements in two-dimensional matrix elements to simulate the stress distribution in the steel/concrete interface. This approach is different from the usual ones in which the steel rebar is replaced by forces and the contribution of the reinforcement stiffness is neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…e use of such a formulation is justified by the capacity and simplicity of its application in the analysis of nonlinear problems as highlighted in Coda and Greco [17] and Greco and Coda [18]. For this reason, although relatively recent, the positional formulation has been the object of study of different researchers, as demonstrated in the works of Coda and Paccola [19], Maciel and Coda [20], Greco and Ferreira [21], de Oliveira and Greco [22], Sampaio et al [23], de Barros Cavalcante et al [24], Pascon and Coda [14], Carrazedo and Coda [25], Rabelo et al [15], and Ramos and Carrazedo [26].…”
Section: Introductionmentioning
confidence: 99%
“…e use of such a formulation is justified by the capacity and simplicity of its application in the analysis of nonlinear problems as highlighted in Coda and Greco [17] and Greco and Coda [18]. For this reason, although relatively recent, the positional formulation has been the object of study of different researchers, as demonstrated in the works of Coda and Paccola [19], Maciel and Coda [20], Greco and Ferreira [21], de Oliveira and Greco [22], Sampaio et al [23], de Barros Cavalcante et al [24], Pascon and Coda [14], Carrazedo and Coda [25], Rabelo et al [15], and Ramos and Carrazedo [26].…”
Section: Introductionmentioning
confidence: 99%
“…2.4 Kinematics coupling strategy Paccola and Coda (2016) and Ramos and Carrazedo (2020). It consists of writing the nodal positions of the reinforcement elements according to the nodal positions of the matrix elements.…”
Section: Finite Element Kinematics Of Rebarsmentioning
confidence: 99%
“…Reinforced composite materials, such as concrete, are easily modelled by the Positional FEM employing embedded techniques. With this technique, the structure stiffness is composed by the contribution of the domain (concrete matrix), fiber (rebars) and particle elements (coarse aggregates), and does not require nodal coincidence between discretizations, maintaining the overall number of degrees of freedom (Vanalli et al, 2008;Radtke et al, 2010;Radtke et al, 2011;Sampaio et al, 2013;Paccola et al, 2015;Paccola and Coda, 2016;Ramos and Carrazedo, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Besides the authors' familiarity with the aforementioned positional formulation of the Finite Element Method, one of the motivations for using it in the present paper is due to its simplicity and applicability in analyses of nonlinear problems as highlight by the precursory authors of the formulation (Coda and Greco, 2004;Maciel and Coda, 2008). For this reason, although relatively recent, the positional formulation has been the object of study by several researchers, as demonstrated in the works of Coda and Paccola (2007), Greco and Ferreira (2009), Oliveira and Greco (2014), Sampaio et al (2015), Cavalcante et al (2017), Pascon and Coda (2017), Carrazedo and Coda (2017), Rabelo et al (2018), Fernandes et al (2018), and Ramos and Carrazedo (2020).…”
Section: Introductionmentioning
confidence: 99%